(3QSGdI aj GdcGahQs - (3CHh Ydj CMeO Hf YHO GdQMef , GHf efOhjg GdCUagGfjs
(3ChdgG (B:s
(3bGd CHhYdj dMb eGbjd dh ScJ ef dGjYde, jSbW ENJdGa , hPdc Cf GdENJdGa aj GdTF EfeG ef Jcde GdLgd ajg HeG dGjYdeg s
(3BNQgG (B:s
(3agPG eG MVQfj ef Gdbhd aj GdcGahQ hCfcQ Cf jchf ajg eYJQV , hdG CLMO efg eGjfJgi Yd ehVY dNdd ajg hGddg hdi GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B166 - (3U(B168s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B110 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj (B(1538) s
Keywords: (3GdWHs